Status and treatment of deserters in international armed conflicts - Niebergall-Lackner, Heike (International humanitarian law series, 2016)
Defining desertion -- The deserter and his of her home country -- The deserter and the enemy party -- The deserter in a country of refuge -- Conslusion and outlook